If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 17 = 3y + 5 Reorder the terms: 17 + y = 3y + 5 Reorder the terms: 17 + y = 5 + 3y Solving 17 + y = 5 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 17 + y + -3y = 5 + 3y + -3y Combine like terms: y + -3y = -2y 17 + -2y = 5 + 3y + -3y Combine like terms: 3y + -3y = 0 17 + -2y = 5 + 0 17 + -2y = 5 Add '-17' to each side of the equation. 17 + -17 + -2y = 5 + -17 Combine like terms: 17 + -17 = 0 0 + -2y = 5 + -17 -2y = 5 + -17 Combine like terms: 5 + -17 = -12 -2y = -12 Divide each side by '-2'. y = 6 Simplifying y = 6
| -7x-3=-6(x+2) | | 7(-5)+2y=11 | | -2c+5c-7c= | | 8x+7=9x+10 | | y+1=-4 | | 14=a-4.5 | | 2/5b+1=4 | | 7(d-3)+10= | | 5h=35 | | 10x+x+4-5=7x-5 | | 700/55 | | 0.85x+.05(16-x)=.10(-120) | | y-8+2y=4 | | -9(x+8)+5=-67 | | y=-.7(50)+123 | | 6-2x=8x-4 | | 2x*2x=3x | | y=-.7(40)+123 | | 6x+5y=150 | | 3/11a=9 | | 1/3(x-7)=5x-4(x-1)+19/3 | | 10+x=2x+3 | | y=-.7(30)+123 | | 5x+4y=38 | | 1/3(x+7)=5x-4(x-1)+19/3 | | x=3/4x+3 | | y=-.7(20)+123 | | a-3=5-a | | 3a*3a=6a | | x-5870.75=3520 | | y=-(1)+4 | | y=-(-0)+4 |